Суконне виробництво в містах і містечках Волинської губернії (кінець XVIII ст. – початок 1860-х років) - Карліна, Оксана Миколаївна; Karlina, Oksana N. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Проаналізовано розвиток суконного виробництва в міських населених пунктах Волинської губернії наприкінці XVIII ст. – початку 1860-х років. Зроблено висновки про кількісне домінування купецьких ману-фактур так званого розсіяного типу, але за обсягом виготовленої продукції та технічним оснащенням виділялися підприємства, які належали землевласникам. Суконне виробництво на Волині, орієноване на потреби армії та на споживання на внутрішньому ринку, ґрунтувалося на використанні місцевої сировини. It was analyzed the development of production of cloth in urban settlеments of Volyn province in the end of XVIII century – the beginning of the 1860s. It was made the conclusions about the quantitative dominance of merchant manufactories so-called scattered type, but for the volume of manufactured products, its product range and the technical equipment the companies, which belonged to the large landowners, were stood out. They attracted foreign colonists to develop the production of cloth on their estates. The largest centers of the cloth industry of Volyn province in the middle of the XIX century were the town Slavuta (Zaslavsk district) and the town Rozhysche (Lutsk district). Focused on the needs of the army and on the consumption in the domestic market, the production of cloth in Volyn was based on the use of local raw stuff.
The Production of Cloth in the Cities and Towns of Volyn Province (the end of XVIII century – the Beginning of the 1860 s).
Keywords: Volyn province; the industrial revolution; the production of cloth; manufactory, merchant's capital; Волинська губернія; купецький капітал; мануфактура; промисловий переворот, суконне виробництво